Identification and characterisation of the Plasmodium vivax rhoptry-associated protein 2 (2005)
Plasmodium vivax is currently the most widespread of the four parasite species causing malaria in humans around the world. It causes more than 75 million clinical episodes per year, mainly on the Asian and American continents. Identifying new antigens to be further tested as anti-P. vivax vaccine candidates has been greatly hampered by the difficulty of maintaining this parasite cultured in vitro. Taking into account that one of the most promising vaccine candidates against Plasmodium falciparum is the rhoptry-associated protein 2, we have identified the P. falciparum rhoptry-associated protein 2 homologue in P. vivax in the present study. This protein has 400 residues, having an N-terminal 21 amino-acid stretch compatible with a signal peptide and, as occurs with its falciparum homologue, it lacks repeat sequences. The protein is expressed in asexual stage P. vivax parasites and polyclonal sera raised against this protein recognised a 46 kDa band in parasite lysate in a Western blot assay.